The Adobe Photoshop book for digital photographers - Kelby, Scott (Voices that matter., 2023)
This update to his award-winning, record-breaking book does something for digital photographers that has never been done beforeit cuts through the bull and shows you exactly how to do it. Its not a bunch of theory; it doesnt challenge you to come up with your own settings or figure it out on your own. Instead, Scott shows you step by step the exact techniques used by todays cutting-edge photographers, and best of all, he shows you flat-out exactly which settings to use, when to use them, and why. Thats why editions of this book are widely used as the official study guide in photography courses at colleges and universities around the world. The photographers workflow in Photoshop has evolved greatly over time and, in the latest edition of this book, youll learn how to leverage Photoshops new AI-powered masking features and how to spend less time on boring production tasks, so you can spend more time being creative.